The role of right ventricular longitudinal function in non-responder patient following cardiac resynchronization therapy. (4th February 2022) - Jenei, C; Toth, A; Nagy, L; Clemens, M; Papp, E; Csanadi, Z
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Hungarian Government Research Fund, Szív- és érkutatási kiválóságközpont (IRONHEART) Background: In approximately 30-40% of cases, the left ventricular systolic function does not improve following cardiac resynchronization therapy (CRT; non-responders). Currently, the role of right ventricular (RV) systolic function is yet not well established. Our aim was to assess the RV systolic function with 3D echocardiography in CRT patients. Methods: We involved 24 patients (12–12 CRT responder and non-responder) who received CRT in our department, and whose 1-year follow-up data were available. We considered the patients "responder" when the left ventricular ejection fraction (LV EF) improved with at least 10% after CRT implantation. We characterized several 3D and 2D parameters of RV using a dedicated RV analysis software, such as RV ejection fraction (EF), body surface area-indexed end-diastolic (EDVi) and end-systolic (ESVi) volumes, free-wall longitudinal (RV GLS) and radial strains. Results: After the follow-up, LV EF was 43 ± 8% in responders and 26 ± 7% in non-respoders (p < 0.0001). RV EF was significantly higher (EF: 44 ± 9%; p = 0.003) in responders compared to non-reponders (EF: 32 ± 9%). There was no significant difference in RV EDVi: 65 ml/m² (IQR: 54-74) in responders and 53 ml/m2 (IQR: 42-67) in non-responders (p = 0.22). RV ESVi was also comparable between CRT responders (37 ml/m² - IQR: 28-39) and non-responders (36 ml/m² - IQR: 28-46), (p = 0.85). RV GLS was significantly higher in CRT responders (-13 ± 3% vs. -10 ± 4% in non-responders; p = 0.02) in parallel with the change of the RV EF, while the RV radial strains did not differ between the two groups (2.5 ± 1.7% in responders vs. 2 ± 1% in non-responders; p = 0.47). Conclusions: The lower RV EF based on mainly the longitudinal function of RV indicates non-respondence to CRT, however, it is not associated with RV dilation, i.e. adverse remodelling. These results suggest mechanical abnormality of RV function in the background of impaired EF.